Quality assurance: framework of indicators and evaluation models for career guidance - Fonzo, Concetta; Serradel-Lopez, Enric (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Based on the already explored domains of guidance, the literature shows how to get informed about new research and developments in quality assurance and evidence-base in career and guidance-related interventions. The current work was situated within the devolved theories about quality (Plant, 2004; Sultana, 2012) and indicators (Hooley, 2014) for effective career guidance provision. A large body of research has been conducted to show how to analyse the quality of guidance and manage measures for ensuring the quality of lifelong guidance services. The study focused primarily, though not exclusively, upon research findings from European quality assurance models and frameworks aimed at identifying, gathering and analysing quality indicators for different guidance providers. Accordingly, the paper focuses on the lessons learned from the research findings designed to inform and consolidate professionals’ understanding and articulation of what constitutes effective guidance-related services.